Analisis Alternatif Penyelesaian Kinerja Persimpangan (Studi Kasus: Persimpangan Jalan HR. Soebrantas-Jalan Kubang Raya-Jalan Garuda Sakti) - M Galang Rosyandi; Sri Djuniati; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The non-functioned traffic lights at intersection point of Jl. HR. Soebrantas-Jl. Kubang Raya-Jl. Garuda Sakti, Pekanbaru, is the main factor that lead to an increase in degree of saturation to 0,962. The value of degree of saturation is greater than the requirement of Indonesian Highway Capacity Manual (IHCM, 1997) which is 0,85. The IHCM method was used to overcome the congestion problem at this intersection point by specifying 4 alternatives solution. There was an increase in DS value by 8,64% for initial condition in alternative 1, a decrease in DS value by 4,78% from alternative 2, a drecrease in DS value by 2,09% for alternative 3 and a decrease by 20,26% in alternative 4. Hence, from the result shown, it is believed that alternative 4 is the best alternative to overcome the congestion problem at this particular intersection point.Keywords: intersection of Jl. HR. Soebrantas-Jl. Kubang Raya-Jl. Garuda Sakti, DS (Degree of saturation), traffic flow.